Wise social studies teaching in an age of high-stakes testing : essays on classroom practices and possibilities - Yeager, Elizabeth Anne, 1960-; Davis, O. L. 1928- (Research in curriculum and instruction., 2005)
The chapters in this volume illustrate how teachers are bringing creativity, higher-order thinking, and meaningful learning activities into particular school settings despite pressures of standards and testing. We chose the word wise for the title of this book, and we use it frequently to describe the pedagogical practices we have identified. The words powerful and ambitious are used as well. The larger point, as Keith C. Barton makes in his chapter, is that there is no necessary connection between content standards and high-stakes tests on the one hand, and lowlevel, rote instruction on the other. He reminds us, as Thornton (1991) and Wiggins (1987) previously have argued, that "teachers play a crucial role in mediating educational policy, and their intentions and interpretations have at least as much influence on classroom practice as does the content of standards and highstakes tests." Barton also asserts that "this makes it all the more crucial to identify the wisdom of practice that enables teachers . . . to engage students in powerful educational experiences."